Analysis of the Cultural Identity of Characters on Fanfiction Adaptation "Atuy Galon" by Cyn - Ardhia Haedar Watiningrum; M. Misbahul Amri; Johannes Ananto Prayogo (VELES Voices of English Language Education Society, 2023)
Atuy Galon is a unique fanfiction that began as a series of short stories on social media, eventually gaining prominence and being published in a comic strip format. What sets this work apart is its distinctive use of slang language, an ever-evolving linguistic phenomenon that resonates particularly with younger audiences. The central figures in the narrative, Atuy, Anton, and Sahrul, not only use slang but each has developed their own distinct slang lexicon, reflecting varied facets of cultural identity. As language remains paramount in shaping one's cultural self-awareness, this research meticulously examines the linguistic choices of these characters. Employing a descriptive qualitative approach alongside a rigorous discourse analysis methodology, the study aims to decode the linguistic intricacies within Atuy Galon and their broader implications for cultural identity formation. The significance of this exploration extends beyond literary analysis; it offers a window into the dynamic interplay between language, culture, and identity among today's youth. Additionally, it underscores the transformative power of technology in reshaping linguistic norms and practices.